2011
DOI: 10.1021/bi2005009
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in a Helix-1 Motif of the ATP Synthase c-Subunit of Bacillus pseudofirmus OF4 Cause Functional Deficits and Changes in the c-Ring Stability and Mobility on Sodium Dodecyl Sulfate–Polyacrylamide Gel Electrophoresis

Abstract: The ATP synthase of the alkaliphile Bacillus pseudofirmus OF4 has a tridecameric c-subunit rotor ring. Each c-subunit has an AxAxAxA motif near the center of the inner helix, where neutralophilic bacteria generally have GxGxGxG. Here, we studied the impact of four single and six multiple Ala-to-Gly chromosomal mutations in the A16xAxAxA22 motif on the capacity for non-fermentative growth and, for most of the mutants, on ATP synthesis by ADP + Pi-loaded membrane vesicles at pH 7.5 and 10.5. SDS-PAGE analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…The A16/20G mutants exhibited the most pronounced phenotype of the alanine mutants. The double mutant defect, described previously, was more severe in a screening assay involving a single 14-h A 600 measurement than in a growth curve experiment conducted under different conditions (24). Interestingly, the extA16/ 20G double mutant grew somewhat better compared with its nonextended homolog on malate at both pH values.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…The A16/20G mutants exhibited the most pronounced phenotype of the alanine mutants. The double mutant defect, described previously, was more severe in a screening assay involving a single 14-h A 600 measurement than in a growth curve experiment conducted under different conditions (24). Interestingly, the extA16/ 20G double mutant grew somewhat better compared with its nonextended homolog on malate at both pH values.…”
Section: Resultsmentioning
confidence: 68%
“…In a previous site-directed mutagenesis study, we showed that selected alanine-to-glycine mutations, all of which included an A16G change, shifted the c-ring migration profiles on SDS gels (24,26). To uncover structural evidence that these mutant B. pseudofirmus OF4 ATP synthases have altered c-ring stoichiometries, we analyzed their c-rings on the single protein complex level by AFM and at the c/c-subunit contacting interface by X-ray crystallography.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations